Shaping Tourist Destinations Through Language and Visual Elements on Tourism Websites: A Tourism Discourse Perspective - Arfin Muhammad Salim, Muhammad; Puad Mat Som, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
Official tourism website has become an essential aspect in shaping tourist destinations. Tourism websites are an essential tool in shaping the norms and values of the destinations which travelers have to visit â€” however, only very few research which focused on the integration of the language element and visual element in shaping tourist destination images. Thus, this study aims to investigate how effective is the use of language and visual elements in shaping the tourist destination on the tourism websites of Sulawesi Selatan, Indonesia. This research employed a discourse approach to analyze both language and visual elements. Data was collected via online documentation and semi-structured interview and analyzed using both textual and visual analysis. The use of lexical and syntactical aspects in the official tourism websites in Sulawesi Selatan, Indonesia are the focus of textual analysis. Furthermore, visual elements such as modality and salience are also looked over. The findings reveal that both, textual and visual elements, complement each other as tourism discourse resources, in realizing Indonesiaâ€™s tourism destinations as attractions on official tourism websites (OTWs).Â Â